MODEL LITERASI DIGITAL PEMBELAJARAN AKIDAH BERBASIS KEBANGSAAN DI PERGURUAN TINGGI UMUM - Achmad Muhibin Zuhri; Winarto Eka Wahyudi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: This paper aims to discuss the faith learning strategies that mainstream the national spirit as one of the human values for students. This study found its relevance because today universities are in the spotlight because their existence is actually fostering the seeds of radicalism, which certainly plays diametrically with human reason. Not only carried out by students, lecturers and professors even justified movements that could potentially create subversion movements in the Republic of Indonesia. Recognizing this phenomenon, then unraveling the tangled thread of the learning process of faith in the field of higher education becomes a necessary effort. For this reason, a learning strategy of faith is needed that can become a tool to strengthen nationalism. The learning strategies in question include: One, internalizing the spirit of nationalism and sensitivity to local culture as the buffer zone of the NKRI pillar. Two, strengthen the tradition of digital literacy in the context of Islamic education. As the main intake of millennial generation, consumption of religious information through the internet must be balanced with the ability to operate digital information. Three, strengthen religious narratives that are more tolerant and humanist in order to strengthen the spirit of national unity.Keyword: Digital Literacy, Faith, University, Nationality